2021
DOI: 10.1097/cm9.0000000000001851
|View full text |Cite
|
Sign up to set email alerts
|

CCT4 suppression inhibits tumor growth in hepatocellular carcinoma by interacting with Cdc20

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…27 For example, CCT4 can promote the proliferation and migration of HCC. 9 In the present study, we found that CCT4 was highly expressed in human ESCC cells and tissues, and was closely associated with poor prognosis, suggesting the important role of CCT4 in the tumorigenesis and progression of ESCC. Besides, CCT4 knockdown inhibited the growth, colony formation, and migration of ESCC cells.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…27 For example, CCT4 can promote the proliferation and migration of HCC. 9 In the present study, we found that CCT4 was highly expressed in human ESCC cells and tissues, and was closely associated with poor prognosis, suggesting the important role of CCT4 in the tumorigenesis and progression of ESCC. Besides, CCT4 knockdown inhibited the growth, colony formation, and migration of ESCC cells.…”
Section: Discussionsupporting
confidence: 55%
“…CCT8 is highly expressed in glioma and further improves the proliferation and invasion of glioblastoma 8 . Similarly, upregulation of CCT4 promotes the proliferation, metastasis, invasion, and cell cycle progression of HCC cells 9 . Therefore, abnormal CCT expression is closely related to tumor formation and progression, which is expected to become potential cancer targeted therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the sum of the correlations of these 385 genes in gastrointestinal cancer, we screened the 30 genes with the strongest correlations, which are RARS1, BTF3, HSPA4, NSA2, HNRNPA1, EIF3M, CCT4, OLA1, UIMC1, G3BP1, NACA, RSL1D1, ETF1, MRPS27, RBM22, CCT8, GEMIN5, LARS1, PA2G4, CDK7, NIFK, RSL24D1, EIF3E, THG1L, INTS13, UBE2D2, RPS23, DIMT1, RIOK2, and TTC27 respectively. Previous studies have reported that overexpression of BTF3, CCT8, CDK7, ELF3M, G3BP1, HSPA4, OLA1, and RSL1D1 can contribute to the occurrence and development of CRC ( Goh et al, 2011 ; Zhou et al, 2019 ; Zhou et al, 2021b ; Liao et al, 2021 ; Zhang et al, 2021 ; Liu et al, 2022a ; Liu et al, 2022b ; Li et al, 2022 ), overexpression of CCT4 and PA2G4 can contribute to the occurrence and development of LIHC( Li et al, 2021a ; Sun et al, 2022 ), overexpression of DIMT1 and HNRNPA1 can contribute to the occurrence and development of STAD ( Liu et al, 2017 ; Zhu et al, 2022 ), and overexpression of EIF3E and UIMC1 can contribute to the ESCA occurrence and development ( Xu et al, 2018 ; Yang et al, 2018 ). Therefore, we believe that these genes have the potential to be called diagnostic and therapeutic targets of gastrointestinal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…NOP58 is not only negatively related to the OS of HCC patients, but may also be closely related to the recurrence of lung adenocarcinoma ( Shen et al, 2021 ; Wang et al, 2021 ). CCT4 is involved in protein metabolism and is significantly related to HCC cell growth and prognosis ( Li F. et al, 2021 ; Li W. et al, 2021 ). In addition, downregulation of CCT4 can significantly inhibit the migration of lung adenocarcinoma cells ( Tano et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%